Pre-pregnancy and early pregnancy dietary patterns and gestational diabetes risk among Miao women in China - Zhang, Song; Ni, Xiaorong; Qiao, Tian; Zhao, Danqing; Shen, Liming; Liang, Yi (Frontiers in Nutrition, 2026)
BackgroundGestational diabetes mellitus (GDM) affects 5–17% of pregnancies globally. However, research on the relationship between dietary patterns and GDM risk is scarce in Asia, especially among ethnic minority groups. This study explored the links between pre-pregnancy and early pregnancy dietary patterns and the risk of GDM in Miao pregnant women in China.MethodsIn this prospective cohort study, we recruited 683 Miao pregnant women and assessed dietary intake using validated food frequency questionnaires covering the year before conception and early pregnancy. Principal component analysis identified major dietary patterns, and multivariable logistic regression models evaluated associations with GDM risk. Restricted cubic spline analysis examined dose-response relationships between traditional Miao foods and GDM.ResultsAmong participants, 130 women (19.03%) developed GDM. Two distinct dietary patterns emerged: a “prudent” pattern (whole grains, vegetables, fruits, beans, nonprocessed meat, eggs) and a “processed” pattern (processed meat, snacks, convenience foods, dessert, beverages). Higher adherence to the pre-pregnancy prudent pattern was associated with significantly reduced GDM odds (highest vs. lowest quartile: OR: 0.49; 95% CI: 0.24, 0.97; P-trend=0.049). Similarly, early pregnancy adherence to the prudent pattern demonstrated a significant inverse association with GDM risk in fully adjusted models, with the highest quartile showing a 56% reduction in risk (OR: 0.44; 95% CI: 0.22, 0.89; P-trend = 0.031). No significant association was observed between the processed pattern and GDM risk after adjustment for potential confounders. Sour soup consumption exhibited protective associations during both study periods, with significant overall associations during preconception (P = 0.044) and early pregnancy (P = 0.011).ConclusionsAdherence to a prudent dietary pattern during preconception and early pregnancy is associated with a reduction in GDM risk among Miao women. Miao traditional sour soup was found to protect against GDM. These findings suggest that promoting healthy dietary habits, particularly focusing on traditional dietary practices, may be an effective strategy for reducing GDM risk in this population.